Synthesis of Algorithms and Procedures for Real-Time Internal Calibration of Receiving Channels in Digital Phased Antenna Arrays - V. H. Tran; M. Th. Hoang; V. B. Nguyen; B. N. Phung (Известия высших учебных заведений России: Радиоэлектроника)
Introduction. Real-time calibration is essential for maintaining the performance of modern digital phased antenna array (DPAA) systems. Previous papers have proposed a method of real-time internal calibration for all receiving channels. This method uses a calibration signal (CalSig) of the same frequency spectrum as the received signal, modulated in phase and amplitude by the binary phase-shift keying (BPSK) and on–off keying (OOK) codes, respectively. With the purpose of improving the method, we propose an algorithm for estimating the phase and amplitude parameters of each receiving channel on the basis of continuous phase correlation accumulation of CalSig samples.Aim. Synthesis of algorithms and procedures for real-time internal calibration of receiving channels in digital phased antenna arrays.Materials and methods. Calibration algorithms and calibration procedure were analyzed and synthesized using the methods of systems analysis. In addition, the methods of systems engineering and technology, digital processing of radar signals and synthesis of building test models close to actual requirements were applied.Results. The advantage of the proposed calibration algorithm and calibration procedure consists in using CalSig modulated by the BPSK and OOK codes. The results obtained on a small DPAA system with four receiving channels gave the error of phase and amplitude lower than 0.3° and 0.05 dB, and the error of main beam direction lower than 0.2°. The results of testing the developed DPAA model confirmed the simplicity and high calibration accuracy of the approach under study.Conclusion. The proposed calibration algorithm and calibration procedure have the advantage over those proposed in previous research in terms of simplicity and resource efficiency. This fact determines the prospects for using the obtained results.